Pengaruh Model Cooperatif Learning Tipe Jigsaw terhadap Hasil Belajar Akidah Akhlak Siswa Kelas VII MTs Al-Khoiriyah Tapos Depok - Siti Nurasiyah; Muhammad Fahri; Ikhwan Hamdani (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
In an effort to improve the quality of education, it is also necessary to have an update in the field of education. One of the efforts to improve the quality of learning is by updating relevance or teaching and learning model approaches. It is said to be good and relevant if a teaching model during the learning process has succeeded in delivering it to achieve an educational goal. The purpose of this study was to determine the effect of cooperative learning or jigsaw type cooperative learning on the learning achievement of seventh grade students at MTs Al-Khoiriyah Tapos, Depok City. The method used in this study, entitled